The Impact of the COVID-19 Pandemic on Aboriginal Economic Development Corporations (AEDCs), 2019–2021: An Interview-based Perspective with CEOs - Coates, Kenneth; Finnegan, Greg (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2023)
Collaborating with the Canadian Council on Aboriginal Business (CCAB), the authors investigate how Aboriginal Economic Development Corporations (AEDCs) responded to and, in most cases, weathered the commercial disruptions associated with the COVID-19 pandemic. Working from survey interviews, supplemented by business data from previous CCAB national surveys and other governmental information, the authors explore the challenges that CEOs faced and how they managed their companies through the COVID crisis. For many of the AEDCs respondents, the problems they were facing were not necessarily brought on by the pandemic but were outgrowths of pre-existing socioeconomic disparities that had been exacerbated by COVID-19. Throughout the pandemic, these CEOs battled to maintain operations, manage and support staff in trying circumstances, and keep their assets operating or safely managed. They frequently assisted their home communities with services not normally within their purview, including producing PPE products and delivering groceries and medicine to remote communities. This report focuses on crisis management and can be a useful reference point for policymakers and decision-makers looking to create coherent responses to whatever the next crisis faced by EDCs might be.